(3ceGd GdOjf hJeGe GdfYeI ai GKHGJ GdZjHI hcTa GdMjQIs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3CMeO GdehShjs)
(3ChdgG (B:s
(3HGH eG Qhj Yf GdUGOb LYaQ Hf eMeO Ydjg GdSdGe ef GdfU Ydi GdbGFe (B...s
(3BNQgG (B:s
(3Ef GdYHO EPG GNJGQg Gddg JYGdi dCehQ YHGOg jTQM dPdc UOQg hChOY bdHg jfGHjY GdMceI(B....s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B274s
(3EjVGM Gdecfhf(B:(3L(B2(3,U(B381s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds